(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2024)
A key element of cardiovascular disease are stenoses and occlusions of blood vessels which are generally treated by endovascular interventions like percutaneous transluminal angioplasty. Our objective was to develop a 3D-printed, versatile, reversible and multi-use stenosis intended for patient individualized training and research purposes. We conducted a preliminary evaluation of this stenosis in a 3D-printed femoral artery phantom by performing a simulated balloon angioplasty.